The Influence of Profitability and Leverage on Stock Prices (Case Study of Coal Sub-Sebtor Companies on the IDX Period 2019-2021) - Chika Dewianty; Seflidiana Roza; Nurhayati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of profitability and leverage on share prices of coal sub-sector companies on the IDX for the 2019-2021 period. The financial ratios studied are Profitability (ROA) and Leverage (DER). The population in this research are coal sub-sector companies on the IDX for the 2019-2021 period. The sample consisted of 23 companies that published complete financial reports for 3 years (2019-2021) using the purposive sampling method, namely a sample selection technique using certain criteria that the researcher had determined for the object under study. Data collection was carried out using documentation methods and accessing the web and related sites. Data analysis was carried out using multiple linear regression analysis. The research results show that the profitability variable has a partially significant effect on stock prices. Meanwhile, the Leverage variable does not have a partially significant effect on stock prices. Simultaneously, it was found that share prices and leverage jointly influence share prices with R2 0,354 (35,4%). Keywords: Profitability, Leverage, Share Price